THE PRE-CONTRACTUAL DUTY OF DISCLOSURE IN THE PALESTINIAN CIVIL CODE DRAFT AND ITS ROLE IN MAINTAINING ECONOMIC CONTRACTUAL EQUILIBRIUM (UUM Journal of Legal Studies, 2021)
Many recent legislations and international principles tend to apply the pre-contractual duty of disclosure as one of the most substantial principles governing the pre-contracting phase, such as Article 1112-1 of the Amended French Civil Code of 2016, Article 1337 of the Amended Italian Civil Code and Article 13 of chapter 2 of the Common European Sales Law, etc. However, the Palestinian legislature has ignored enacting legal provisions imposing the pre-contractual duty of disclosure which causes legislative deficiencies in the legislative remedies of the subject of pre-contractual duty of disclosure. In this regard, this paper suggests orientations for the formulation of the provisions of the pre-contractual duty of disclosure in the Palestinian Civil Code Draft (PDCC). To do so, a comparative analytical approach with the French civil code is used to illustrate the Palestinian legislative deficiencies and the urgent need to legislate a legal article which obligates the negotiating party to disclose any substantial information for the satisfaction of the other party. As such, the contractual equilibrium entails that the pre-contractual duty of disclosure has its own independent essence from all the theories that the jurisprudence adopted as a legal basis for this duty.